Kompleksitas Penyelenggaraan Akreditasi Berbasis Online pada Lembaga PAUD - Siti Mutingah; Novan Ardy Wiyani (JECED : Journal of Early Childhood Education and Development, 2022)
Online-based PAUD accreditation is not without problems. There are various problems that show the complexity of the implementation of online-based PAUD accreditation at PAUD institutions in Banyumas district. This study aims to describe and analyze the complexity that occurs in the implementation of online-based accreditation at PAUD institutions in Banyumas district. This study uses a quantitative method that is descriptive in nature where the researcher can describe the results of the research that has been carried out by describing the object of research at the current state based on the actual facts then analyzed and interpreted. Based on the results of the research, the findings were in the form of obstacles or problems faced in implementing online PAUD accreditation including: (1) lack of guidance related to the eight National PAUD Education Standards; (2) lack of assistance in filling in the EDS-PA on the Sispena application; (3) teachers' limited ICT skills; and (4) limited internet network in PAUD institutions.